Properties of entire solutions of differential equations - Sheremeta, Z. M.; Sheremeta, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We investigate the close-to-convexity and l-index boundedness of entire solutions of the differential equations $z^2w'' + β zw' + (γ z^2 — β)w = 0$ і$ zw'' + β w' + γ zw = 0$.